Perisai Keadilan Korban Kesalahan Pemberitaan Oleh Pers (Universitas Musamus, 2023)
The existence of this study is intended to analyze concretely factual problems of restoring the rights of victims of misreporting by the Press in constitutional and constitutional terms and other laws and regulations. This research will be carried out with normative legal research methods accompanied by a statute approach and a conceptual approach (conceptual approach) which of course is based on primary, secondary, and tertiary legal materials that still have relevance to the topic of discussion with legal reasoning techniques. In fact, the media does have the power to have an impact on what it has been informed that can affect the attitudes and behavior of a person or group in the sense of society so that it has views in accordance with the information obtained. The media can influence people's views in forming public opinion and this will cause a lot of losses, where victims who receive these losses experience difficulties in the mechanism to restore their rights that have been harmed because the binding legal basis is still not contained in existing regulations. So it is necessary to carry out preventive efforts as a form of protection and law enforcement by carrying out prevention through regulations in legal products regarding the restoration of the rights of victims of wrong reporting by the press. Keywords: restorative, press, preaching